Trends in Child Protection Across the UK: A Comparative Analysis. (17th October 2017) - Bunting, Lisa; McCartan, Claire; McGhee, Janice; Bywaters, Paul; Daniel, Brigid; Featherstone, Brid; Slater, Tom
Abstract: Although numerous international studies point to large variations in child welfare interventions, comparative analysis has tended to focus either solely on England or the UK as a whole, discounting differences across the four UK countries. This paper compares trends in national statistics relating to the operation of child protection systems across England, Scotland, Wales and Northern Ireland between 2004/05 and 2013/14. Despite a number of legislative, operational and definitional differences between nations, a number of trends are apparent. All systems show an increasing orientation towards child protection as evidenced by rising rates of child protection investigation and children subject to child protection planning. Increasingly, this relates to emotional abuse and involves younger children aged from birth to four years. However, the way cases are processed can differ, with only one in ten referrals resulting in a child protection investigation in Northern Ireland compared to one in five in England. Potential reasons for these differences are discussed and questions raised as to why, more than a quarter-century after the introduction of the 1989 Children Act, we still have no clear picture of the circumstances of families who come into contact with social services or the services provided to support them.